Implementation of Lemon Aromatherapy for Acute Pain Management in Post-Laparotomy Appendicitis Patient at Bayu Asih Hospital - Nurmala Nurmala; Ike Puspitaningrum (Indonesian Publication Center, 2026)
Acute postoperative pain is a common problem that affects patient comfort and the recovery process. This study aims to describe the application of lemon aromatherapy to reduce acute pain in postoperative patients at Bayu Asih Regional Hospital, Purwakarta. This study used a descriptive case study approach involving a 20-year-old female patient with acute postoperative pain following laparotomy appendicitis. Data were collected periodically through interviews, observations, physical examinations, and documentation. The treatment intervention used lemon aromatherapy inhalation, applying three drops of lemon essential oil to the tissue and inhaling it for 30 minutes in seven sessions over three days. Initial assessments indicated that the patient experienced moderate pain (pain scale of 5), accompanied by grimacing, restlessness, nausea, increased heart rate, and increased blood pressure. Evaluation results on the third day showed a significant decrease in pain intensity to a scale of 2 (mild pain), improved vital signs, and decreased behavioral responses such as grimacing and protective behaviors. The findings suggest that lemon aromatherapy can stimulate the limbic system and increase endorphin release, thereby helping to reduce postoperative pain intensity. Therefore, lemon aromatherapy can be considered a complementary non-pharmacological intervention in postoperative pain management.